Pengaruh Promosi Online, Brand Image Dan Shopping Lifestyle Terhadap Impulse Buying Pada E-Commerce Shopee (Studi Pada Mahasiswa Universitas Panca Marga) - Amalia, Tiara Indah; Bahri, Mohammad Saiful; Widayanto, Mutinda Teguh (Universitas Panca Marga, 2024)
This research was conducted at Panca Marga University with the aim of finding out the influence of online promotions, brand image and shopping lifestyle on impulse buying. The type of research used is quantitative research with a causal associative approach. The population was Panca Marga University students with a sample of 94 respondents and the sampling technique used Probability Sampling with the Proportionate Stratified Random Sampling method. The data analysis methods used are validity tests, reliability tests, classical assumption tests, multiple regression analysis, coefficient of determination and hypothesis testing. The results of this research show that online promotion has a significant effect on impulse buying on Shopee e-commerce, brand image has a significant effect on impulse buying on Shopee e-commerce, shopping lifestyle has a significant effect on impulse buying on Shopee e-commerce, online promotion, brand image, and shopping lifestyle simultaneously have a significant effect on impulse buying on Shopee e-commerce.